Clinical Presentation of Myocarditis in Children Visiting Dr Ruth KM PFAU, Civil Hospital, Karachi. A Cross-Sectional Study - Waheed Ahmed, Muhammad Saad Raza, Yousuf Yahya, Suneet Kumar, Rumana Sangi, Kashif Habib Qadri, Musarat Nazir (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of various clinical presentations of myocarditis in children visiting to Dr Ruth KM PFAU, Civil Hospital Karachi. Study design: Cross-Sectional Study. Place and duration: Department of Pediatric Medicine, Dr Ruth K.M PFAU Civil Hospital, Karachi, Pakistan from September, 2020, to March, 2021 Methodology: The study covered all patients who visited Karachi’s Civil Hospital and met the inclusion criteria. After describing the study’s process, hazards, and benefits, informed consent was obtained. The initial ECG, echocardiography, and cardiac enzyme readings were all documented. Stroke, congenital heart disease, sepsis, asthma, pulmonary embolism, cardiomyopathy, gastroenteritis, diabetes mellitus, and renal failure were among the clinical presentations that were noted. The proforma that is supplied at the end was filled out with all the acquired data and used electronically for research. Results: Age was 6.8± 2.1 years on average. A total of 238 (67.6%) of the 352 patients were male, and 114 (32.4%) were female. In patients with myocarditis who presented clinically, renal disease was found in 46 (13.1%), cardiomyopathy in 30, congenital heart disease in 56 (15.9%), stroke in 41 (11.5%), gastroenteritis in 65 (18.5%), diabetes mellitus in 19 (5.4%), sepsis in 32 (9.2%), and asthma in 48 (13.6%) patients, while pulmonary embolism was found in 15 (4.3%) patients. Practical implication There is growing evidence to support the use of tests such as cardiac magnetic resonance imaging and serum N-terminal B-type natriuretic peptide measurements as supplements to clinical diagnosis. These could eventually lessen the need for invasive procedures like endomyocardial biopsy, which is still the gold standard. Conclusion: The most frequent clinical manifestation of myocarditis was gastroenteritis, which was followed by congenital heart disease and asthma. For the purpose of validating the results so far, additional extensive research is advised. Keywords: Clinical Presentation, Myocarditis, Epidemiology, Asthma, Gastroenteritis